Juridical Review on Intellectual Property Related to Corporate Intellectual Capital in Indonesia - Shelly Kurniawan; Demson Tiopan (Budapest International Research and Critics University, 2022)
Intellectual properties are not only beneficial to their creators, but also to the common public who uses the products and/or services that contains protected intellectual properties. The more intellectual properties created, the better for the subject of law or the incorporated and non-incorporated business entity since it increases intellectual capital value of the person or the business entity. The purpose of the author in analysing this matter is to qualitatively review the relation between intellectual property and the increase of intellectual property value of a corporation and whether the change of regulation in Act number 11 of 2020 on Job Creation affects a corporation’s intellectual capital in Indonesia. The authors didn’t find any similar research on the topic that the author chose in this study. The method of this research is normative-juridical in nature and takes references from secondary literatures including Act number 11 of 2020 on Job Creation, regulations regarding intellectual properties, books, journals, and articles related to intellectual properties and intellectual capitals. This research shows that the more a corporate owns intellectual properties that yields sales, the more intellectual capital said corporate acquire. The change of regulation regarding trademarks in Act number 11 of 2020 on Job creation may impact on the intellectual capital in terms of capital structure, while the change of regulation regarding the establishment of patent may increase intellectual capital in all categories which are human capital, structure capital, and physical/customer capital.